Albie's first word : a tale inspired by Albert Einstein's childhood - Tourville, Jacqueline (Schwartz & Wade books, 2014)
Because three-year-old Albie, who would one day be known as Albert Einstein, has never spoken his concerned family takes him to a doctor who recommends a series of activities that might stimulate him to talk.